"Circularly polarized 4 × 4 MIMO antenna for WLAN applications". Issue 5 (4th July 2019) - Subhanrao Bhadade, Raghunath; Padmakar Mahajan, Shrinivas
ABSTRACT: A circularly polarized (CP) 4 × 4 MIMO antenna with low mutual coupling is proposed to operate at 2.4 GHz WLAN band (IEEE 802.11b/g/n/ax) applications. The proposed design consists of four CP pentagonal microstrip elements with suspended substrate and five loaded slits to obtain the high gain and required impedance bandwidth. The CP elements are orthogonally arranged with diagonal element has same CP to reduce mutual coupling among the elements. The proposed MIMO antenna exhibits impedance bandwidth 170 MHz, a peak gain 7.95 dBd, and axial ratio ≤3 dB. More than 30 dB isolation is achieved between two elements. The MIMO antenna performance in terms of diversity gain (DG), efficiency, and envelope correlation coefficient (ECC) has been reported.